Upcycling date juice waste: Impact of date press cake on sponge cake quality - Golsa Karambakhsh; Mohammad Taghi Golmakani; Parisa Houshmandi; Asgar Farahnaky; Mahsa Majzoobi (Food Chemistry: X)
Date press cake (DPC) is the main waste stream of date fruit juice extraction. The primary aim of this research was to explore the potential of DPC as a novel food component, using sponge cake as a case study, to upcycle waste from date fruit processing. Thus, different concentrations (0 %, 10 %, 20 %, 30 %, and 40 %) and particle sizes (210 and 500 μm) of DPC were tested on the quality characteristics during storage for 1, 7, and 14 days. While the protein content remained constant, a decrease in particle size was found to increase the fat content from 4.48 % to 5.37 % and decrease the fiber content from 14.35 % to 9.13 %. In addition, the consistency and density of the cake batter increased while increasing the concentrations and decreasing the DPC particle sizes. The height, volume, cohesiveness, and springiness of the cake decreased, and its density, hardness, gumminess, and chewiness increased, by decreasing the DPC particle sizes, the increase in its levels and the storage days.